Compensation of Regional Unemployment in Housing Markets - Wouter Vermeulen; Jos van Ommeren (Tinbergen Institute, 2005)
Why are regional unemployment differentials in Europe so persistent if, as the wage curve literature demonstrates, there is no compensation in labour markets? We hypothesize that workers in high-unemployment regions are compensated in housing markets. Modelling regional unemployment differentials as a consequence of centralized wage bargaining, we show that clearing of land markets may undo the incentive for workers to migrate to low-unemployment regions in general equilibrium. The compensating differentials hypothesis is tested on city-level data for several countries. Controlling for variation in income and amenities, housing is found to be about 3 percent less expensive on average in cities where unemployment is 10 percent up. An analysis of housing demand survey data, which takes account of housing heterogeneity, yields a similar negative relationship. The magnitude of the income effect generated by this compensating differential is consistent with a -0.10 wage curve elasticity. These findings weaken the case for regional support programs.
Keywords: R23; R13; J64; 330; regional unemployment; housing markets; wage curve; compensating differentials; hedonic models; regional policy